2022
DOI: 10.3389/fphys.2022.871912
|View full text |Cite
|
Sign up to set email alerts
|

Refining Our Understanding of the Flow Through Coronary Artery Branches; Revisiting Murray’s Law in Human Epicardial Coronary Arteries

Abstract: Background: Quantification of coronary blood flow is used to evaluate coronary artery disease, but our understanding of flow through branched systems is poor. Murray’s law defines coronary morphometric scaling, the relationship between flow (Q) and vessel diameter (D) and is the basis for minimum lumen area targets when intervening on bifurcation lesions. Murray’s original law (Q α DP) dictates that the exponent (P) is 3.0, whilst constant blood velocity throughout the system would suggest an exponent of 2.0. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In this retrospective study, we have validated a regionalized porous wall boundary method for simulating side branch Q and compared the results with those from the original homogeneous method. 15 The main aim of this work was to regionalize the side branch and main branch flow. This was achieved with no major difference in overall side branch flow compared with the homogeneous method.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this retrospective study, we have validated a regionalized porous wall boundary method for simulating side branch Q and compared the results with those from the original homogeneous method. 15 The main aim of this work was to regionalize the side branch and main branch flow. This was achieved with no major difference in overall side branch flow compared with the homogeneous method.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, one direct in-vitro validation of virtuQ outlet Q results has been performed, reporting a bias of +2.08 ± 3.45 mL/min 13 and our previous validation of inlet Q CFD using the homogeneous porous wall boundary method reported zero bias between CIT results with 95% limits of agreement of ±168 mL/min. 15 More data are available for the latest, monorail Rayflow catheter design. An in-vitro trial of Q CIT reported a bias of −6.5 ± 15.5 mL/min 12 and one animal study reported a bias of +5 ± 8 mL/min from Q measured in 12 pigs (mean Q 37 mL/min).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations